Microbiota e aspectos físico-químicos do leite materno, perfil de sensibilidade microbiana in vitro e detecção de genes de enterotoxinas clássicas de Staphylococcus sp. - Zanini, Dayane da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Health agencies around the world recommend exclusive breastfeeding until the child is six months old and continued until two years of age, due to its fundamental role in the development of the newborn, due to its nutrient-rich composition. Studies have shown the role of food microbiota in infant intestinal development. However, the role of some groups such as enterobacteria, a group considered contaminating, which can compromise the milk offered for donation, is still unclear. The present study evaluated the presence of microorganisms in breast milk from Milk Banks, sent for routine analysis, and identified the microorganisms isolated by mass spectrometry (MALDI-TOF MS), evaluated the sensitivity profile to antimicrobials and detected classical enterotoxin genes in isolates identified as Staphylococcus spp. The results showed the identification of 13 genera and 30 different species, the most common being Staphylococcus spp. The in vitro sensitivity test against nine antimicrobials revealed a resistance rate of the isolates to penicillins and beta-lactam derivatives (36%) and macrolides (45,35%). However, there was greater efficacy of gentamicin and trimethoprim sulfamethoxazole. Five bacterial species were multidrug resistant (MDR), with the highest percentage for K. oxytoca (66%). The search for classical enterotoxin genes (A, B, C, D and E) was carried out using conventional PCR, resulting in six of the 72 staphylococcal isolates being positive for sea. The study showed a high variety of microorganisms that can be found in breast milk, and the identification of multi-resistant isolates, warning of the rational use of antimicrobials, in addition to the presence of enterotoxin genes, an important staphylococcal virulence factor.

Agências de saúde ao redor do mundo recomendam o aleitamento materno exclusivo até os seis meses de idade da criança e sua continuidade até os dois anos, devido ao papel fundamental no desenvolvimento do recém-nascido, pela sua composição rica em nutrientes. Estudos têm mostrado o papel da microbiota do alimento para o desenvolvimento intestinal do lactente. Contudo ainda não está claro o papel de alguns grupos como as enterobactérias, um grupo considerado contaminante, que pode comprometer o leite oferecido para doação. O presente estudo avaliou a presença de micro-organismos no leite materno de Banco de Leite, encaminhado para análises de rotina, e identificou os micro-organismos isolados por espectrometria de massas (MALDI-TOF MS), avaliou o perfil de sensibilidade aos antimicrobianos e detectou genes de enterotoxinas clássicas nos isolados identificados como Staphylococcus spp. Os resultados mostraram a identificação de 13 gêneros e 30 espécies diferentes, sendo mais recorrente Staphylococcus spp. O teste de sensibilidade in vitro ante nove antimicrobianos, revelou uma taxa de resistência dos isolados às penicilinas e derivados betalactâmicos (36%) e aos macrolídeos (45,35%). Por outro lado, houve maior eficácia da gentamicina e sulfametoxazol trimetoprim. Cinco espécies bacterianas foram multirresistentes (MDR), com maior percentual para K. oxytoca (66%). A pesquisa de genes de enterotoxinas clássicas (A, B, C, D e E) foi realizada por PCR convencional, resultando em seis dos 72 isolados de estafilococos, positivos para sea. O estudo mostrou alta variedade de micro-organismos que podem ser encontrados no leite materno, e a identificação de isolados multirresistentes alertando para o uso racional de antimicrobianos, além da presença de genes de enterotoxinas, importante fator de virulência estafilocócica.
Microbiota and physicochemical aspects of breast milk, in vitro microbial sensitivity profile and detection of classical enterotoxin genes from Staphylococcus sp.
Keywords: Leite materno; Banco de leite humano; Microbiota; Multirresistência; Breast milk; Human milk bank; Microbiota; Multidrug resistance